(untitled) - Baran, Stanley J. (New York, 2006)
This text encourages students to take more active roles as media consumers and gives them a deeper understanding of the role that the media play in both shaping and reflecting culture. Through this cultural perspective, students learn that audience members are as much a part of the mass communication process as are the media producers, technologies, and industries. This was the first university-level text to make media literacy central to its approach; building on this tested emphasis, the new updated edition features dozens of updates on recent technologies and government rulings, including the Patriot Act, the Supreme Court ruling on Peer-2-Peer file-sharing on Grokster, the National Cable and Telecommunications Association vs. Brand X, newspaper blogs, BitTorrent, podcasting, and much more
Keywords: Mass media,Mass media and culture,Media literacy